Peningkatan Hasil Belajar Pendidikan Agama Islam Melalui Penerapan Metode Pembelajaran Simulasi Pada Siswa Kelas V SD Negeri 114 Seluma - Etri, Lori (JURNAL ILMU PENDIDIKAN, 2023)
This study discusses the improvement of learning outcomes in Islamic Religious Education through the application of the simulation learning method for SELUMA 114 Elementary School students. This study aims to determine: 1). How to apply the simulation learning method in Islamic Religious Education lessons for SDN 114 SELUMA students, 2). What are the learning outcomes of Islamic Religious Education for students of SDN 114 SELUMA, 3). How to increase the learning outcomes of Islamic religious education through the application of the simulation learning method for SDN 114 SELUMA students. This type of research is Classroom Action Research (CAR), which consists of two cycles with three meetings and one evaluation. Research procedures include planning, implementing observation and evaluation and reflection. The results showed that of the first cycle of 42 students, only 36 met the Maximum Completeness Criteria (KKM), classically not fulfilled because the average score was 70.00, or in the low category. Where in cycle II of the 42 students there were 40 students who met the Maximum Completeness Criteria (KKM) and classically had been fulfilled, namely the average value of 90.00 or was in a high category